2019
DOI: 10.1002/hep.30284
|View full text |Cite
|
Sign up to set email alerts
|

UBE3A Suppresses Overnutrition‐Induced Expression of the Steatosis Target Genes of MLL4 by Degrading MLL4

Abstract: Regulation of the protein stability of epigenetic regulators remains ill-defined despite its potential applicability in epigenetic therapies. The histone H3-lysine 4-methyltransferase MLL4 is an epigenetic transcriptional coactivator that directs overnutrition-induced obesity and fatty liver formation, and Mll4 mice are resistant to both. Here we show that the E3 ubiquitin ligase UBE3A targets MLL4 for degradation thereby suppressing high fat diet (HFD)-induced expression of the hepatic steatosis target genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 45 publications
(167 reference statements)
1
11
0
Order By: Relevance
“…However, continuous CORT exposure did lead to a statistical interaction between AS and CORT treatment in the liver transcriptome, which suggests that UBE3A may regulate GR activity in a tissue-specific manner. The observed changes in the liver transcriptomic response to continuous CORT treatment are in line with AS mice susceptibility to hepatic dysfunction [34].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, continuous CORT exposure did lead to a statistical interaction between AS and CORT treatment in the liver transcriptome, which suggests that UBE3A may regulate GR activity in a tissue-specific manner. The observed changes in the liver transcriptomic response to continuous CORT treatment are in line with AS mice susceptibility to hepatic dysfunction [34].…”
Section: Discussionsupporting
confidence: 68%
“…Disrupted GR signaling in the hippocampus of UBE3A-deficient AS mice has been associated with learning disabilities and anxiety-like behavior [33]. Furthermore, UBE3A-deficient AS mice are known to be hypersensitive to diet-induced liver steatosis [34], and previously showed metabolic disturbances resulting from an altered circadian rhythm [35]; characteristics that have been related to disruptions in GR signaling [36][37][38]. However, the molecular mechanisms underlying the UBE3A modulation of GR signaling are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…MLL4 was defined as a critical regulator of overnutrition that induced obesity and hepatic steatosis [ 50 ]. Moreover, Ube3a suppressed overnutrition-induced NAFLD by targeting and degrading MLL4 [ 51 ]. Calcoco1, Smarca2, Cln3, Tacc1, and Gm38366 were coexpressed with Lpin1 and Ube3a.…”
Section: Discussionmentioning
confidence: 99%
“…While much effort has been devoted to studying the transcriptional regulation of metabolic pathways during the development of hepatic steatosis, little is known about the post-translational modification of metabolic enzymes in this process, especially through ubiquitination-mediated mechanisms. Therefore, we employed a unique approach based on the OUT platform to identify the metabolic enzymes as ubiquitination targets of UBE3A, which has been shown to prevent HFD-induced hepatic steatosis in mice . We further verified the ubiquitination of PDHA1 and ACAT1 by UBE3A in HEK293 cells and studied the physiological role of UBE3A in regulating the stabilities of its substrate proteins and lipid metabolism in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Due to genomic imprinting, the Ube3a gene is paternally inactivated in the brain, so its UB ligase activity is vulnerable to mutations in the maternal copy of the gene that may render the gene defective and cause the delay of neuronal and intellectual development in children. , On the other hand, the duplication of the Ube3a gene in the maternal chromosome is associated with autism spectrum disorders. , Ube3a is normally expressed from both paternal and maternal copies of the chromosome in the peripheral tissues. The binding of the E6 protein of the human papillomavirus (HPV) with UBE3A would induce the degradation of the tumor suppressor p53, which is causative for the development of cervical cancer. , UBE3A has been recently shown to play a role in hepatic steatosis . In this study, we identified two essential enzymes regulating glycolysis, the TCA cycle, and ketogenesis, namely pyruvate dehydrogenase A1 (PDHA1) and acetyl-CoA acetyltransferase 1 (ACAT1), as ubiquitination targets of UBE3A.…”
Section: Introductionmentioning
confidence: 99%